Drop impact testing for Pb-freee aloy on IC packaging - Ismail, Noor Faezah; Sulaiman, Nasri; Md Yunus, Nurul Amziah (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Soldering is one of the techniques for interconnects which provides the conductive path from one circuit to others circuit element. In the other hands, soldering cover pats of its structural strength, electrical connection, grounding and signal transmission. The process of interconnection must be in a proper way so that it will produce a good interconnection while a bad interconnection can cause a weak adhesion, which lead to bad results and minimize the lifetime of the devices. The heavy the weight of object, the stronger impact force will be experienced.